Beneficial Effect of Phenytoin and Carbamazepine on GFAP Gene Expression and Mutant GFAP Folding in a Cellular Model of Alexander’s Disease - Bachetti, Tiziana; Zanni, Eleonora Di; Adamo, Annalisa; Rosamilia, Francesca; Sechi, M. Margherita; Solla, Paolo; Bozzo, Matteo; Ceccherini, Isabella; Sechi, GianPietro (Frontiers in Pharmacology, 2021)
Alexander’s disease (AxD) is a rare, usually relentlessly progressive disorder of astroglial cells in the central nervous system related to mutations in the gene encoding the type III intermediate filament protein, glial fibrillary acidic protein (GFAP). The pathophysiology of AxD is only partially understood. Available data indicate that an excessive GFAP gene expression may play a role. In particular, it has been reported a “threshold hypothesis” suggesting that mutant GFAP representing about 20% of the total cellular GFAP should be sufficient to cause disease. Thus, strategies based on reduction of cellular mutant GFAP protein levels and/or the activation of biological processes involved in the correct protein folding could be effective in counteracting the toxic effect of misfolded GFAP. Considering that clomipramine (CLM), which has been selected by a wide small molecules screening as the greatest inhibitory potential drug against GFAP expression, is controindicated because of its proconvulsant activity in the infantile form of AxD, which is characterized also by the occurrence of epileptic seizures, two powerful antiepileptic agents carbamazepine (CBZ) and phenytoin (PHT), which share specific stereo-chemical features in common with CLM, were taken into consideration in a reliable in vitro model of AxD. In the present work we document for the first time that CBZ and PHT have a definite inhibitory effect on pathological GFAP cellular expression and folding. Moreover, we confirm previous results of a similar beneficial effect of CLM. As CBZ and PHT are currently approved for use in humans, their documented inhibitory effect on pathological GFAP cellular expression and folding may indicate a potential therapeutic role as disease-modifying agents of these drugs in clinical management of AxD, particularly in AxD patients with focal epilepsy with and without secondary generalization.